Changes in Air Temperature in Poland at Around Noon in the Years 1951-2018 (Geography and Tourism, 2019)
The paper characterises the variability of thermal conditions in Poland at around noon in the years 1951–2018. Based on the data from Kołobrzeg, Poznań and Kraków, the average monthly, seasonal and annual values of air temperature were calculated along with standard deviation, maximum and minimum temperature values, as well as the average values of temperature in the consecutive decades of the studied period. Moreover, values of linear trends were determined along with statistical significance at a level of 0.05, as well as values of the deviations of temperature from a long-term average, which were smoothed by means of 10-year moving averages. The research indicated a statistically significant increase in air temperature, both annual and in individual seasons. Particularly noticeable warming was noted in the winter-spring period, especially in Krakow; the smallest one occurred in autumn. The increase in temperature in the studied years was influenced mostly by the years 2011–2018. Also, higher contrast of thermal conditions compared to other seasons of the year was observed in the winter-spring season.